487. Analysis of the Association between Specific Antibody Response against Respiratory Syncytial Virus Fusion Protein Conformations and Life-Threatening Infection in Previously Healthy Infants. (15th December 2022) - Bonnin, Florencia A; Talarico, Laura B; Phung, Emily; Kumar, Azad; Ferolla, Fausto M; Byrne, Alana B; Acosta, Patricio L; Toledano, Analía; Caratozzolo, Ana; Contrini, María M; Graham, Barney S; Ruckwardt, Tracy; et al.
Abstract: Background: Specific humoral response against pre-fusion (pre-F) conformation of respiratory syncytial virus (RSV) F protein has been proposed to play a role against severe infection. We aimed to analyze the association between serum IgG titers against pre-F and post-fusion (post-F) conformations of RSV F protein and life-threatening RSV disease (LTD) in previously healthy infants. Methods: Prospective cohort study including previously healthy infants < 12 months, hospitalized with a first RSV infection, in 2017-2019. Patients were defined to have LTD when required intensive care and ventilatory support. Pre-F exclusive and post-F-specific antibody responses were determined by post-F competition and non-competitive immunoassays, respectively, and neutralizing activity was measured by plaque reduction neutralization test. Viral load (VL) was assessed by qRT-PCR from nasopharyngeal aspirates collected on admission. Serum samples were collected within 72 h from admission and in convalescence (between 14 to 60 days). Results: Seventy-five patients were included, median age 3 months, 60% (n=45) were males; 21 patients developed LTD. Importantly, acute and convalescent post-F and pre-F exclusive IgG titers did not associate with LTD (Fig 1). There was a positive correlation between neutralizing antibody titers and pre-F exclusive IgG titers ( p =0.016). Post-F and pre-F exclusive IgG titers negatively correlated with age in acute phase ( p < 0.0001 and p = 0.0009). In acute phase, post-F and pre-F exclusive IgG titers were higher in patients ≤ 2 months (Fig 2). Patients > 2 months increased post-F and pre-F exclusive IgG titers in convalescence. Additionally, post-F and pre-F exclusive titers did not correlate with VL, and VL was not related to LTD. Conclusion: -Pre-F exclusive and post-F IgG titers did not associate with LTD, even though pre-F exclusive IgG correlated with neutralizing antibody titers. -Infants under two months of age developed a lower humoral response, likely due to an interference by maternal antibodies and/or immunological immaturity. -These findings highlight the importance of fully characterizing the immune response against RSV and its association with disease severity for the development of preventive strategies. Disclosures: Barney S. Graham, MD, PhD, BSG: BSG is an inventor on patents for the stabilization of the RSV F protein (WO2014160463A1, Prefusion RSV F proteins and their use).|National Institutes of Health: Inventor on patents for RSV vaccines|National Institutes of Health: inventor on patents for measles and other paramyxovirus vaccines.